Two novel virulence loci, mxiA and mxiB, in Shigella flexneri 2a facilitate excretion of invasion plasmid antigens. - Andrews, G P (1991)
A bank of over 4,200 lacZ protein fusions in Shigella flexneri 2a was screened for fusions to temperature-regulated promoters. One mutant, BS260, was completely noninvasive on HeLa cells and mapped to a region on the 220-kb virulence plasmid in which we had previously localized several avirulent temperature-regulated operon fusions (A.E. Hromockyj and A.T. Maurelli, Infect. Immun. 57:2963-2970, 1989). The phenotype of BS260 was similar to that of the previously identified mxi (membrane expression of invasion plasmid antigens) mutants, since it made wild-type intracellular levels of the invasion plasmid antigens (Ipa) but was deficient in the surface expression of IpaB and IpaC. Six kilobases of DNA upstream of the BS260 fusion end joint were cloned, but no temperature-regulated promoter was found, whereas the fusion end joint clone of the noninvasive mxi operon fusion mutant BS226 contained a temperature-regulated promoter. The locus defined by BS260 was designated mxiA, and that defined by BS226 was designated mxiB. Closer analysis of the mxiA and mxiB phenotypes by a cell-free enzyme-linked immunosorbent assay revealed that the mutants failed to excrete IpaB and IpaC into the culture medium, whereas wild-type cells actively released these antigens. Excretion of the ipa polypeptides from wild-type bacteria was confirmed by Western blot analysis of culture supernatants. Protease protection experiments revealed that wild-type S. flexneri 2a actually had much lower levels of surface-exposed IpaB and IpaC relative to those in the total antigen pool. In addition, examination of cellular fractions showed that, although there was no IpaB or IpaC in the outer membrane of BS260 and BS226, the antigens did accumulate in the cytoplasmic membrane. A 76-kDa temperature-regulated polypeptide in wild-type S. flexneri was identified as the putative mxiA gene product. These results strongly suggest that IpaB and IpaC represent truly excreted proteins of S. flexneri and that the mxiA and mxiB loci on the plasmid code for accessory proteins required to facilitate their export through the bacterial outer membrane. These data also suggest that mxiA is part of an operon that specifies additional mxi genes. The products of this operon may constitute a unique multicomponent protein secretion apparatus involved in the transport of Shigella virulence determinants.